2013
DOI: 10.1128/jcm.01587-13
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Treatment Algorithm for Streptococci and Enterococci from Positive Blood Cultures Identified with the Verigene Gram-Positive Blood Culture Assay

Abstract: Bloodstream infections (BSI) are a leading cause of morbidity and mortality. In 2009, BSI were the cause of nearly 36,000 deaths in the United States (1). Health care-associated BSI are a major contributor to these statistics, being associated with nearly 75,000 infections a year with a mortality rate of approximately 25% (2). Enterococci are the third leading cause of health careassociated BSI (3), and inappropriate antimicrobial therapy has been shown to be an independent risk factor for the increased mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…These include fluorescence in situ hybridization (FISH), matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), and nucleic acid amplification or detection assays (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). While each approach has specific strengths and weaknesses, all have demonstrated their potential to positively impact key indicators, such as laboratory turnaround time, length of hospital stay, cost of care, and overall mortality associated with BSI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include fluorescence in situ hybridization (FISH), matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), and nucleic acid amplification or detection assays (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). While each approach has specific strengths and weaknesses, all have demonstrated their potential to positively impact key indicators, such as laboratory turnaround time, length of hospital stay, cost of care, and overall mortality associated with BSI.…”
mentioning
confidence: 99%
“…Selection of the BC-GP or BC-GN assay is based on the primary Gram stain result of a positive blood culture broth. Several studies have reported on the performance of the BC-GP assay, which has a sensitivity ranging from 96% to 100% and Ͼ98% specificity for the majority of targets (18,21,24,25). The BC-GN assay has also been evaluated; however, studies to date have included Ͻ150 blood cultures or have included primarily simulated specimens (20,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Several papers have already evaluated the Verigene panel dedicated to Gram-positive bacteria (8)(9)(10)(11)(12), but this is the first one on the BC-GN test. To investigate its potential clinical usefulness, we evaluated the following parameters: (i) the concordance of identification and of antibiotic susceptibility data with those obtained with the traditional blood culture flowchart, (ii) the time to definitive results, and (iii) the impact of the BC-GN test results on ongoing empirical therapy, evidencing the rate of potential BC-GN-induced antibiotic changes.…”
mentioning
confidence: 99%
“…The ability to reliably identify a specific bacterium or yeast present in a positive blood culture within 1 to 3 h of culture positivity using these methods has resulted in significant reductions in time to effective antimicrobial therapy, length of hospital/intensive care unit (ICU) stay, 30-day mortality, and cost of care (6,7,(11)(12)(13). Importantly, while organism identification alone can provide some benefit, the most significant benefits are achieved when the presence of resistance markers, such as mecA, vanA, or carbapenemases, is identified concomitantly (11,12,(14)(15)(16).The research-use-only (RUO) iC-GPC assay (iCubate, Huntsville, AL) is a molecular target amplification assay capable of detecting and identifying Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumoniae, Enterococcus faecalis, and Enterococcus faecium as well as the genetic resistance determinants mecA, vanA, and vanB directly from positive blood culture broths. The system consists of an automated processor (iC-Processor), a reader (iC-Reader), and single-use, closed-system test cassettes.…”
mentioning
confidence: 99%
“…The ability to reliably identify a specific bacterium or yeast present in a positive blood culture within 1 to 3 h of culture positivity using these methods has resulted in significant reductions in time to effective antimicrobial therapy, length of hospital/intensive care unit (ICU) stay, 30-day mortality, and cost of care (6,7,(11)(12)(13). Importantly, while organism identification alone can provide some benefit, the most significant benefits are achieved when the presence of resistance markers, such as mecA, vanA, or carbapenemases, is identified concomitantly (11,12,(14)(15)(16).…”
mentioning
confidence: 99%